Impelementasi Evaluasi Pembelajaran Fiqih Di Madrasah Tsanawiyah Muhammadiyah Alamanda Kabupaten Pasaman Barat - Suharjo; Remiswal; Asril, Zainal (Arus Jurnal Pendidikan, 2023)
Based on result of the research that has been done, The implementation of fiqih learning evaluation at Madrasah Tsanawiyah Muhammadiyah Alamanda has achieved a number of achievements but still faces some challenges. The evaluation is conducted holistically, covering the cognitive, affective, and psychomotor aspects of the student. Teachers use various evaluation methods, such as written exams, observations, and projects. The challenges involved limited resources and the use of technology for evaluation. Furthermore, the adaptation of curricula to the evolution of the times and the needs of students became a major concern in improving the effectiveness of the evaluation of fiqih learning. The research recommendations include expanding the use of technology in evaluation, developing training programs for teachers related to evaluation, and improving the curriculum to meet the ever-growing needs of students. By making these improvements, it is hoped that the evaluation of fiqih learning in Madrasah Tsanawiyah Muhammadiyah Alamanda can be more effective in producing an optimal quality of education.